Pengaruh Penerimaan APBD Terhadap Kemandirian Keuangan Kabupaten/Kota di Provinsi Sumatera Barat - M Marzuki; Chairil Akhyar; N Nurlela; Fika Yandani (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2022)
This study aims to examine the effect of local taxes, regional levies, profit-sharing fund general allocation funds and special allocation funds for regional financial independence in districts/cities in West Sumatra Province. This study uses secondary data, namely data obtained from district/city APBD realization reports in West Sumatra Province from 2016-2020 by accessing the official website on the website of the Directorate General of Fiscal Balance and the Regional Financial Agency of West Sumatra Province. The data analysis technique was using panel data regression analysis. The results of the analysis in this study indicate that local taxes and revenue-sharing funds have a significant positive effect on regional financial independence, while special allocation funds have a significant negative effect on regional financial independence. Meanwhile, regional levies and general allocation funds have no significant effect on regional financial independence.